2013
DOI: 10.4103/0019-5278.123168
|View full text |Cite
|
Sign up to set email alerts
|

Profile of ocular trauma in industries-related hospital

Abstract: Introduction:Ocular trauma is a worldwide cause of visual morbidity, a significant proportion of which occurs in the industrial workplace and includes a spectrum of simple ocular surface foreign bodies, abrasions to devastating perforating injuries causing blindness. Being preventable is of social and medical concern.Aim:A prospective case series study, to know the profile of ocular trauma at a hospital caters exclusively to factory employees and their families, to co-relate their demographic and clinical prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
0
13
2
Order By: Relevance
“…Our study raised a frequency of <0.5%, compared to higher reported percentages, ranging from 3% to 10% [4,14,17,18,23,24,25]. Furthermore, the mean prognosis (2.4 ± 1.4 days) was also lower compared to other studies, where values ranging from three days to more than two weeks have been reported [26,27,28].…”
Section: Discussioncontrasting
confidence: 77%
“…Our study raised a frequency of <0.5%, compared to higher reported percentages, ranging from 3% to 10% [4,14,17,18,23,24,25]. Furthermore, the mean prognosis (2.4 ± 1.4 days) was also lower compared to other studies, where values ranging from three days to more than two weeks have been reported [26,27,28].…”
Section: Discussioncontrasting
confidence: 77%
“…The lost work time due to ocular injury from agricultural activities, with its attended fewer lost workdays of restricted activities (3 days), is similar to the finding of studies reported in the literature 33 . The high prevalence of ocular injuries among cocoa farmers in this study may be due to the wide variety of ocular hazards they face in their daily activities on the farm, as well as, the high level of manual labour involved in cocoa farming 18,34,35 . Ocular injuries were a major cause of corneal/ opacity or scars in this study and led to three people experiencing permanent blindness in one eye each.…”
mentioning
confidence: 99%
“…Despite not being a variable with statistical significance, the age group from 40 to 59 years, which represents the mean age of the sample included in the current study, may be a risk factor for the development of ocular manifestations. Other studies have found conflicting data after reporting that workers from 20 to 40 years of age showed a higher risk for occupational ocular manifestations, compared to older workers, (15,16) which may be explained by the fact that younger port workers have little professional training and less working time. In contrast, studies showed a higher risk of ocular manifestations for older workers.…”
Section: Discussionmentioning
confidence: 94%